(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Dal Lake, located in Srinagar, Jammu and Kashmir, is one of India's most iconic freshwater bodies. However, it has undergone severe environmental degradation due to anthropogenic activities, particularly sewage discharge, houseboat waste, and agricultural runoff. This research paper examines how pollutants in Dal Lake water alter its freezing point compared to pure water. Through analysis of existing water quality data, freezing point depression principles, and field observations, we demonstrate that dissolved impurities—primarily nitrogen compounds, phosphorus, calcium, magnesium, and dissolved salts—lower the freezing point of Dal Lake water to approximately −11°C, significantly below the standard 0°C freezing point of pure water (Atkins, 2010; Castellan, 1983; Organic Biotech, 2025). This phenomenon has profound implications for the lake's winter ecology, aquatic life cycles, and regional climate patterns. The paper integrates colligative property theory with empirical data from Dal Lake water quality assessments conducted between 2005 and 2024 (GeoJournal, 2005; IWA Publishing, 2024).